2017
DOI: 10.1016/j.theriogenology.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles of follicular fluid from cows submitted to ovarian superstimulation

Abstract: Ovarian superstimulation with exogenous gonadotropins has been extensively used to produce in vivo-derived embryos for embryo transfer in cattle. This process modifies the antral follicle microenvironment and affects oocyte and embryo quality as well the differentiation of granulosa cells. Lipids play significant roles in the cell, such as energy storage, cell structure, and fine-tuning of the physical properties and functions of biological membranes. The phospholipid (PL) contents as well as the effects of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The animals were maintained on pasture ( Urochloa brizantha ), with ad libitum access to water and a mineral supplement. Nelore ( Bos taurus indicus ) nonlactating multiparous cows of age 5–7 years, and with body condition scores ranging from 2.0 to 3.5, were submitted to P‐36 (FSH group; n = 10) or P‐36/eCG (FSH/eCG group; n = 10) ovarian superstimulation protocols as described previously (Castilho et al, ; Fontes et al, ; Santos et al, ). Briefly, at a random stage of the estrous cycle, all animals received progesterone‐releasing vaginal inserts (1.0 g; PRIMER®, Tecnopec, São Paulo, Brazil) and estradiol benzoate (2.5 mg, i.m., Estrogin®, Farmavet, São Paulo, Brazil) on Day 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were maintained on pasture ( Urochloa brizantha ), with ad libitum access to water and a mineral supplement. Nelore ( Bos taurus indicus ) nonlactating multiparous cows of age 5–7 years, and with body condition scores ranging from 2.0 to 3.5, were submitted to P‐36 (FSH group; n = 10) or P‐36/eCG (FSH/eCG group; n = 10) ovarian superstimulation protocols as described previously (Castilho et al, ; Fontes et al, ; Santos et al, ). Briefly, at a random stage of the estrous cycle, all animals received progesterone‐releasing vaginal inserts (1.0 g; PRIMER®, Tecnopec, São Paulo, Brazil) and estradiol benzoate (2.5 mg, i.m., Estrogin®, Farmavet, São Paulo, Brazil) on Day 0.…”
Section: Methodsmentioning
confidence: 99%
“…When FSH was combined with eCG, genes involved in oviduct contraction, and relaxation were upregulated (Fontes et al, ) along with mRNA‐encoding proteins involved in the LH receptor intracellular signaling in granulosa cells (Castilho et al, ). Furthermore, this hormonal combination was able to modify the lipid profile of follicular fluid and steroidogenic capacity, increase plasma estradiol, regulate the abundance of the VEGF system, and LHCGR mRNA, and suppress miR‐222 expression in bovine granulosa cells (Santos et al, ). However, the eCG effects on cumulus‐oocytes complexes (COCs) and embryo quality remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The search for biomarkers in the FF of PCOS patients undergoing IVF is a cornerstone for understanding how this syndrome affects the ovaries and how it compromises fertility potential to the extent that these patients need ART treatments. It has been previously reported that ovarian superovulation alters the FF lipid composition in cows . In addition, although lipids have been suggested to be indicative of PCOS diagnosis, molecular diagnosis of this condition remains a challenge as it is made in the absence of specific symptoms and without validated molecular markers …”
Section: Resultsmentioning
confidence: 99%
“…For ovarian superstimulation, as described by Santos et al [29], cows at random stages of estrous cycle received progesteronereleasing vaginal inserts (1.0 g, PRIMER ® , Tecnopec, São Paulo, SP, Brazil) and estradiol benzoate (2.5 mg, i.m., Estrogin ® , Farmavet, São Paulo, SP, Brazil) on day 0.…”
Section: Ovarian Superstimulationmentioning
confidence: 99%
“…Therefore, the last two doses of FSH are replaced by eCG doses in the P-36/eCG protocol. Recent data in Nelore cows demonstrated the impact of superstimulatory protocols on the oviductal transcript profile [28], lipid profile of follicular fluid [29], and the expression of genes involved in LHCGR signaling in granulosa cells [30]. However, the effects of P-36 and P-36/eCG protocols on follicular development need further investigation.…”
Section: Introductionmentioning
confidence: 99%